Optimization of Waste Management at the Purwosari Material Recovery Facility (MRF) Mijen District, Semarang City - Anik Sarminingsih; Winardi Dwi Nugraha; Alya Karmilia (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Semarang City is working on constructing a Material Recovery Facility (MRF) in various urban villages to reduce the waste that enters the Jatibarang Landfill. However, the construction of MRF is not optimal. MRF Purwosari still functions as a container without waste processing. By projecting waste generation for the next ten years, the results of optimization planning are processing waste into RDF, redesigning MRF covering an area of 1,571 m2 with an investment cost of IDR 1,602,837,997 and an operational cost of IDR 307,741/ton/day. The NPV value was Rp.4,836,965, EIRR 12%, and BCR value of 1.81.